A new model for cluster dynamics: from strategic to regional networks a study of the development of a French high-tech cluster. (16th April 2007) - Lechner, Christian; Leyronas, Christophe
Clusters are perceived as a factor that increases the international competitiveness of firms that are part of the cluster. Therefore the mechanisms leading to the development of clusters and the effects of clusters on firm competitiveness should be a central issue for international entrepreneurship. The central research questions in this study are: Are there alternative development models for clusters? If so, what does this mean for the competitiveness of clusters and the advantages and disadvantages accruing to the firms in the cluster? To explore these research questions, we conducted a case study investigating a French high-tech cluster. Our case study provides a very different explanation for the competitiveness of clusters and firms than those generally found in the literature. Performance within clusters is highly distributed. These performance differences are a necessary precondition for cluster development. For firms, however, regional competitiveness is the precondition for international competitiveness: firms need to develop a strong position in the regional network in the first place.